Journey to the south: A case study of a Chinese PhD student in a Malaysian university - Zhou Fei; Amran Rasli; Tan Owee Kowang; Goh Chin Fei; Hii Puong Koh (International Journal of Evaluation and Research in Education (IJERE), 2023)
Recent trends indicate that more mainland China students are selecting Malaysian universities to further their studies based on the push-pull model. This study aims to examine their motivation for further studies as well as the obstacles and problems faced by them in Malaysian universities. A case study has been adopted in this study. A purposive sampling technique was employed to identify the right respondent and data collection was conducted through semi-structured interviews. The findings of the research revealed that peer recommendation, comparative advantage, cultural similarity, and self-desire for improvement have a significant influence on the mainland Chinese motivation to further their PhD studies at Malaysian Universities. Existing literature has not paid adequate attention to motivational factors that influence China students to select Malaysian universities to pursue their PhD. Furthermore, this research addressed the shortcoming of classic acculturation models that lacks importance given to how the dominant Malaysian majority can be affected by the acculturation orientations of mainland Chinese students. As such, this paper is an attempt to fill up these gaps. This study provides some practical implications for Malaysian universities with better strategic insight to review their research programs and improve the service quality of their research infrastructure.